The Effects of Anthropogenic Land Use on the Distribution of Butterflies in Negros Oriental, Philippines - Badon, Jade Aster T (Silliman Journal, 2022)
The importance of distributional records for organisms lies in providing supportive documentation as the backbone for conservation planning. A distributional survey of diurnal butterflies was done in the province of Negros Oriental, Philippines to determine the effects of anthropogenic factors on the presence of butterflies in specific localities. One of the most important findings in the survey is that habitats along rivers and lakes provide the last refuge for some species of butterflies. The habitat heterogeneity caused by anthropogenic factors has resulted in the differences in species community and distribution in 16 areas of Negros Oriental examined during this study. The data that were gathered during the survey can be used for preliminary conservation assessments, especially for those species that were distributed in isolated forest patches.